Toxicity screening analysis of dipropyl phthalate, DPP on early vertebrate development - Nur Qistina Diyana, binti Khairul Anwar (Universiti Malaysia Sarawak (UNIMAS), 2016)
Phthalates are most frequently used chemical in industries to make plasticizers and polymer additive in gel capsules, cosmetic, and other personal care products. This study was initiated to enhance our insight on the health and environmental impact on Dipropyl phthalate, DPP - one of the phthalate family. In this study, the effects of dipropyl phthalate on the development of zebrafish embryos and early larval stages were investigated. Eggs were exposed to dipropyl phthalate toxic started from 4 to 96-hour post fertilization (hpf), and defects of the zebrafish larvae examined at 96 hpf. Toxicological endpoints like mortality, hatching delay, pericardial edema, yolk sac edema, non-inflated swim bladder, deformation of the tail, blood island, and mobility were recorded. The LC5o calculated to be 7.546 mg/L. These results suggest that dipropyl phthalate could induce a dose-dependent toxicity in embryos, which hinders normal development.